Peran Negara dan Efektivitas Politik Hukum Nasional Melindungi Keamanan Data dan Hak Privasi Digital - M. Zainun Nasihin; Hwian Christianto (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This article analyzes the role of the state and the effectiveness of national legal politics in ensuring data security and the privacy rights of citizens in the era of digital globalization. The research employs a normative juridical method using statutory, conceptual, and doctrinal approaches, supplemented by an empirical literature review on data breach incidents in Indonesia. Philosophically, personal data protection is grounded in the values of humanity and justice embodied in Pancasila, and constitutes an integral part of human rights as guaranteed by the 1945 Constitution of the Republic of Indonesia. Juridically, the enactment of Law Number 27 of 2022 concerning Personal Data Protection marks a significant milestone in developing secure and accountable data governance. The findings reveal that the implementation of this regulation remains weak, as evidenced by the absence of an independent data protection authority, the lack of comprehensive implementing regulations, poor inter-agency coordination, and low public literacy regarding digital security. From the perspective of legal politics, the state's response to digital security challenges tends to be reactive and has yet to become fully progressive in accordance with technological advancements. This article asserts that the state must function not only as a regulator but also as a facilitator and protector by strengthening the legal framework, enhancing cyber resilience, establishing an independent data protection authority, and promoting international collaboration. Through a progressive and responsive legal approach, the state can safeguard privacy rights while upholding digital sovereignty amid the rapid expansion of global digitalization.